Understanding the e-Wom and consumer behavior: a conceptual study in hospitality and tourism / Muhammad Syamim Mohd Ikram - Mohd Ikram, Muhammad Syamim (2021)
This study purpose is to evaluate the current studies regarding e-WOM and consumer behavior in hospitality industry. Besides that, this study aims to compare the findings from empirical research that conducting on related studies and providing some general considerations. Two research objectives have been acknowledge in this study and method for this study is on qualitative study to analyze e-WOM and consumer behavior in hospitality industry. This study review passes research as the secondary sources to gather the information required in order to achieve the objectives of the study. Such information has been collected mainly from journal article that conduct on the relationship of e-WOM and consumer behavior in hospitality industry. Findings in the study show that influencing factor impacted the usage of e-WOM in the means of positive and negative consumer perspective. Other than that, this research shows five factors affecting consumer behavior on E-WOM which is; Service Quality, Pre-Purchase Expectation, Helping Companies, Social Identity and Failure and Recovery. Thus this research achieved the purpose of the study by analyzing e-WOM and consumer behavior in hospitality industry.